The ASEAN experience of the purchasing power parity theory - S. M. Woahid Murad; Mohammad Amzad Hossain (Financial Innovation, 2018)
We used panel data analysis to evaluate the relative purchasing power parity (PPP) hypothesis of the ten ASEAN member countries between 1973 and 2015. We incorporated the cross-sectionally augmented panel unit root test as proposed by Pesaran (J Appl Econ 22:265-312, 2007). For panel cointegration analysis, we employed the four error-correction-based Westerlund (Oxf Bull Econ Stat 69:709-748, 2007) panel cointegration tests. The Westerlund (Oxf Bull Econ Stat 69:709-748, 2007) tests are general enough to permit a large degree of heterogeneity, both in the long-run cointegrating relationship and in the short-run dynamics, and dependence within as well as across the cross-sectional units. To check the robustness of the results, we further estimated the cointegration test excluding Indonesia and Brunei. The findings support our initial results. Further, all the results overwhelmingly support the relative PPP hypothesis. Consequently, the monetary authority would be able to implement a self-regulating monetary policy. It would also be able to control the exchange rates.
Keywords: F31; F37; C32; C33; 650; Purchasing power parity; Panel unit root test; Panel cointegration test; ASEAN countries